2021
DOI: 10.1093/brain/awab186
|View full text |Cite
|
Sign up to set email alerts
|

SREBP2 gene therapy targeting striatal astrocytes ameliorates Huntington’s disease phenotypes

Abstract: Brain cholesterol is produced mainly by astrocytes and is important for neuronal function. Its biosynthesis is severely reduced in mouse models of Huntington’s disease. One possible mechanism is a diminished nuclear translocation of the transcription factor sterol regulatory element binding protein 2 (SREBP2) and, consequently, reduced activation of SREBP-controlled genes in the cholesterol biosynthesis pathway. Here we evaluated the efficacy of a gene therapy based on the unilateral intra-stria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 69 publications
4
36
2
Order By: Relevance
“…Expanding on the feature of mHTT-induced neuropathology and loss of normal HTT function (here modeled by the wtHTT 18Q vector construct), alterations in cholesterol and FA metabolism that provide the main components of the myelin sheath and precursors of steroid hormones [60] are also found in HD [61][62][63]. Strategies of cholesterol delivery to the HD brain and targeting the key components Sterol-regulatory element-binding protein 2 (SREBP-2) and Sirtuin 2 (SIRT2) in the striatum can ameliorate disease phenotypes [64][65][66]. Here we found that Stoml3, present in cholesterol-rich lipid rafts and associated with dopaminergic transmission [67], was differentially downregulated in 79Q vs. WT and trended towards downregulation in 18Q vs. WT (p < 0.05 but adj p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Expanding on the feature of mHTT-induced neuropathology and loss of normal HTT function (here modeled by the wtHTT 18Q vector construct), alterations in cholesterol and FA metabolism that provide the main components of the myelin sheath and precursors of steroid hormones [60] are also found in HD [61][62][63]. Strategies of cholesterol delivery to the HD brain and targeting the key components Sterol-regulatory element-binding protein 2 (SREBP-2) and Sirtuin 2 (SIRT2) in the striatum can ameliorate disease phenotypes [64][65][66]. Here we found that Stoml3, present in cholesterol-rich lipid rafts and associated with dopaminergic transmission [67], was differentially downregulated in 79Q vs. WT and trended towards downregulation in 18Q vs. WT (p < 0.05 but adj p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…However, this compound failed in a phase 3 clinical trial for ALS 35 , which could underlie the requirement for a concomitant therapy that compensates for cholesterol in ALS MNs. Furthermore, as shown in Huntington’s disease, SREBP2 gene therapy may be promising for ALS 36 . Taken together, this reverse-translational study could provide a molecular basis for future ALS therapy targeting cholesterol biosynthesis.…”
Section: Discussionmentioning
confidence: 94%
“…SREBP2 is expressed in glial cells, especially in astrocytes and oligodendrocytes, where it controls lipid synthesis ( Camargo et al, 2009 ). Mutant HTT decreases the activity of SREBP2 by 50% in cells and mouse brain tissues ( Valenza et al, 2005 ), and overexpression of its active form in astrocytes, in vitro and in vivo in R6/2 mice, showed beneficial effects in neurons ( Valenza et al, 2015b ; Birolini et al, 2021b ). This suggests an important dialogue between glial and neuronal cells for proper cholesterol homeostasis.…”
Section: Clinical Strategies To Manipulate Cholesterol Metabolism In ...mentioning
confidence: 99%
“…This suggests an important dialogue between glial and neuronal cells for proper cholesterol homeostasis. In this way, in an elegant study, a gene therapy approach was used to express the transcriptionally active form of human SREBP2 specifically in striatal astrocytes of R6/2 mice ( Birolini et al, 2021b ). The authors found a re-activation of the cholesterol pathway biosynthesis, associated with restoration of synaptic transmission, clearance of mHTT aggregates, and improvement of motor defects and cognitive decline.…”
Section: Clinical Strategies To Manipulate Cholesterol Metabolism In ...mentioning
confidence: 99%